Case report: A highly active refractory myasthenia gravis with treatment of telitacicept combined with efgartigimod - Zhang, Chaoyue; Lin, Yangtao; Kuang, Qianjin; Li, Hongjin; Jiang, Qilong; Yang, Xiaojun (Frontiers in Immunology, 2024)
There is always a lack of effective treatment for highly active refractory myasthenia gravis (GMG).Recently, telitacicept combined with efgartigimod significantly reduce circulating B cells, plasma cells and immunoglobulin G, which bring promising therapeutic strategies. We report a case of a 37year-old female patient with refractory GMG, whose condition got significant improvement and control with this latest treament after multiple unsuccessful therapies of immunosuppressants. The new combination deserves further attention in the therapeutic application of myasthenia gravis.